2021
DOI: 10.1007/s00436-021-07105-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immunoprotective effects of recombinant protein and DNA vaccine based on Eimeria tenella surface antigen 16 and 22 in vivo

Abstract: Coccidiosis triggered by Eimeria tenella is accompanied by haemorrhagic caecum and high morbidity. Vaccines are preferable choices to replace chemical drugs against coccidiosis. Surface antigens of apicomplexan parasites can adhere to host cells during the infection process. Therefore, truncated fragments coding E. tenella surface antigen 16 (EtSAG16) and 22 (EtSAG22) were cloned into pET-28a prokaryotic vector to express recombinant protein 16 (rEtSAG16) and 22 (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…This was further confirmed by the subsequent assay in the present study, which showed that chickens immunized with rEtROP17 had a significant increase in IgY titers compared with those of the challenged control and the unchallenged control groups. No significant differences between the challenged and the unchallenged groups in IgY titer were observed, which was consistent with the results of a previous study [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…This was further confirmed by the subsequent assay in the present study, which showed that chickens immunized with rEtROP17 had a significant increase in IgY titers compared with those of the challenged control and the unchallenged control groups. No significant differences between the challenged and the unchallenged groups in IgY titer were observed, which was consistent with the results of a previous study [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…The expression of SAG is differentially regulated between oocyst/zygotes and second-generation cleavage stages, with only one being specifically expressed in the zygotes, a few in both stages, and most in the second generation cleavage ( Tabares et al, 2004 ), with the SAG B gene being specifically expressed in the second-generation cleavage peak expression in the second generation of cleistogamy. In recent years, many researchers have investigated the immunogenicity of SAG proteins, such as SAG1 ( Vo et al, 2021 ), SAG2, SAG4 ( Zhao et al, 2020b ), SAG6, SAG15 ( Geng et al, 2022 ), SAG16, SAG22, SAG23 ( Song et al, 2021 ; Zhao et al, 2021 ), among which SAG1, SAG4, SAG15, and SAG22 have candidate antigenic genes to be anticoccidial vaccines. In general, protective antigens will prefer proteins expressed in the intracellular phase or in the metabolically active phase of the worm, whereas SAG22 belongs to the SAG B gene, which is capable of efficient expression in the second generation of cleavers.…”
Section: Discussionmentioning
confidence: 99%
“…In general, protective antigens will prefer proteins expressed in the intracellular phase or in the metabolically active phase of the worm, whereas SAG22 belongs to the SAG B gene, which is capable of efficient expression in the second generation of cleavers. In a study ( Zhao et al, 2021 ), a truncated fragment encoding the surface antigen SAG22 of E. tenella was cloned into the pET-28 and expressed in the E. coli expression system, the recombinant protein SAG22 has immune protective effect on broilers. However, immune protection was only studied on d 14 chicks, and the immune protection was weak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the emergence of drug resistance to anticoccidial drugs and genetic variants of Eimeria strains, as well as the issue of residual virulence, have been consistently identified as potential risk factors [ 6 , 10 , 11 ]. Increasing scientific evidence indicates that recombinant anticoccidial vaccines are promising alternatives to antibiotics in the control of coccidiosis in poultry [ 12 ]. Over the last decades, recombinant protein technology has become efficient and relatively inexpensive through the use of microbial and other expression host systems [ 13 ].…”
Section: Introductionmentioning
confidence: 99%